Coupling virus-induced gene silencing to exogenous green fluorescence protein expression provides a highly efficient system for functional genomics in arabidopsis and across all stages of tomato fruit development - Quadrana, Leandro Daniel (2011)
Since the advent of the postgenomic era, efforts have focused on the development of rapid strategies for annotating plant genes of unknown function. Given its simplicity and rapidity, virus-induced gene silencing (VIGS) has become one of the preeminent approaches for functional analyses. However, several problems remain intrinsic to the use of such a strategy in the study of both metabolic and developmental processes. The most prominent of these is the commonly observed phenomenon of “sectoring” the tissue regions that are not effectively targeted by VIGS. To better discriminate these sectors, an effective marker system displaying minimal secondary effects is a prerequisite. Utilizing a VIGS system based on the tobacco rattle virus vector, we here studied the effect of silencing the endogenous phytoene desaturase gene (pds) and the expression and subsequent silencing of the exogenous green fluorescence protein (gfp) on the metabolism of Arabidopsis (Arabidopsis thaliana) leaves and tomato (Solanum lycopersicum) fruits. In leaves, we observed dramatic effects on primary carbon and pigment metabolism associated with the photobleached phenotype following the silencing of the endogenous pds gene. However, relatively few pleiotropic effects on carbon metabolism were observed in tomato fruits when pds expression was inhibited. VIGS coupled to gfp constitutive expression revealed no significant metabolic alterations after triggering of silencing in Arabidopsis leaves and a mild effect in mature green tomato fruits. By contrast, a wider impact on metabolism was observed in ripe fruits. Silencing experiments with an endogenous target gene of interest clearly demonstrated the feasibility of cosilencing in this system; however, carefully constructed control experiments are a prerequisite to prevent erroneous interpretation.